2017
DOI: 10.1016/j.eururo.2017.07.015
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Variants Related to Longer Telomere Length are Associated with Increased Risk of Renal Cell Carcinoma

Abstract: Background Relative telomere length in peripheral blood leukocytes has been evaluated as a potential biomarker for renal cell carcinoma (RCC) risk in several studies, with conflicting findings. Objective We performed an analysis of genetic variants associated with leukocyte telomere length to assess the relationship between telomere length and RCC risk using Mendelian randomization, an approach unaffected by biases from temporal variability and reverse causation that might have affected earlier investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…We found that the observed associations between leukocyte telomere length and cancers in the present study (i.e., multiple myeloma, chronic lymphocytic leukemia, kidney/renal cell cancer, bladder cancer, malignant melanoma, basal cell carcinoma, and prostate cancer) are greatly consistent with prior findings obtained in terms of MR ( Supplementary Table S1; Zhang et al, 2015;Ojha et al, 2016;Haycock et al, 2017;Machiela et al, 2017;Li et al, 2020;Went et al, 2020). Particularly, several previous studies demonstrated that a shorter telomere length was associated with a decreased lung cancer risk or mortality and that the association was present in adenocarcinoma while absent in squamous cell carcinoma ( Supplementary Table S1; Zhang et al, 2015;Haycock et al, 2017;Kachuri et al, 2018;Yuan et al, 2018), which may be attributed to the discrepancy in the biological characteristics of various subtypes of lung cancer.…”
Section: Discoveries Combined With the Previous Studysupporting
confidence: 92%
“…We found that the observed associations between leukocyte telomere length and cancers in the present study (i.e., multiple myeloma, chronic lymphocytic leukemia, kidney/renal cell cancer, bladder cancer, malignant melanoma, basal cell carcinoma, and prostate cancer) are greatly consistent with prior findings obtained in terms of MR ( Supplementary Table S1; Zhang et al, 2015;Ojha et al, 2016;Haycock et al, 2017;Machiela et al, 2017;Li et al, 2020;Went et al, 2020). Particularly, several previous studies demonstrated that a shorter telomere length was associated with a decreased lung cancer risk or mortality and that the association was present in adenocarcinoma while absent in squamous cell carcinoma ( Supplementary Table S1; Zhang et al, 2015;Haycock et al, 2017;Kachuri et al, 2018;Yuan et al, 2018), which may be attributed to the discrepancy in the biological characteristics of various subtypes of lung cancer.…”
Section: Discoveries Combined With the Previous Studysupporting
confidence: 92%
“…On the contrary, the genetic risk score has the advantage of being independent from study design and from the environmental factors known to be associated with a variation of LTL. The use of genetic proxies to understand the causative correlation between environmental risk factors and outcome has become more and more popular in the last years and it has been instrumental in identifying several of such associations 23,[36][37][38][39][40][41][42][43] . The sample size of our study is almost four times larger than the average size of the previous studies (480 vs 130) if considering only the cases and almost five times larger if considering cases and controls combined (1389 vs 285).…”
Section: Discussionmentioning
confidence: 99%
“…Telomere length is, at least partially, genetically determined, and 11 SNPs have been identified, through GWAS, to affect LTL 23,34,35 . To overcome the biases of using the direct measure of LTL, the genetic score combination of these 11 SNPs has been successfully used as proxy of genetically determined LTL to investigate its association with various cancer types 23,[36][37][38][39][40][41][42][43] . Noteworthy, the associations between LTL and cancer risk have not consistently shown the same trend if the LTL was measured directly through qPCR or through the genetic score 22,23,36,44 .…”
Section: Introductionmentioning
confidence: 99%
“…One such study used nine telomere length–associated SNPs to create a telomere length surrogate score and found longer telomere length scores associated with lung adenocarcinoma but not the other cancers 159 . Renal cell carcinoma, one of the cancers with reproducible telomere length association data, was also studied using nine telomere length surrogate SNPs and it was found that genetically longer telomeres were associated with renal cell carcinoma 160 .…”
Section: The Advent Of Telomere Molecular Epidemiologymentioning
confidence: 99%